2020
DOI: 10.1111/jep.13472
|View full text |Cite
|
Sign up to set email alerts
|

Communication barriers between basic scientists and clinicians in regenerative medicine: A qualitative study from Iran

Abstract: Rationale, aims, and objectives Cell‐based therapeutics are among the latest advances in health care technologies. The rapid evolution of stem cell science in Iran has necessitated the application of scientific achievements in clinical settings. However, various issues hindered their translation, in particular, impediments in the interactions of basic stem cell scientists and clinicians. We highlighted the impediments in the interactions of stem cell scientists and physicians involved in the opinion of profess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 62 publications
0
6
0
Order By: Relevance
“…Trainees are assessed on adequate completion of coursework, documented scientific progress, and future acquisition of academic positions [ 6 ] The Regenerative Medicine and Surgery Course at Mayo Clinic [ 7 ] The Regenerative Medicine and Surgery Course at Mayo Clinic was created with the goal of increasing student literacy of and interest in regenerative medicine concepts [ 7 ]. Participants in the program include 1st, 2nd, and 4th year medical students, graduate students (Ph.D and MD/Ph.D), PGY-1 and 2 internal medicine residents, and research fellows [ 11 ]. Trainees participate in a series of didactic lectures focused on regenerative medicine principles, daily briefings on clinical trials to understand regenerative approaches within the clinic, laboratory experiences in stem cell culturing and 3D bioprinting, cadaver demonstrations of surgical procedures, and a regenerative medicine career panel [ 7 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Trainees are assessed on adequate completion of coursework, documented scientific progress, and future acquisition of academic positions [ 6 ] The Regenerative Medicine and Surgery Course at Mayo Clinic [ 7 ] The Regenerative Medicine and Surgery Course at Mayo Clinic was created with the goal of increasing student literacy of and interest in regenerative medicine concepts [ 7 ]. Participants in the program include 1st, 2nd, and 4th year medical students, graduate students (Ph.D and MD/Ph.D), PGY-1 and 2 internal medicine residents, and research fellows [ 11 ]. Trainees participate in a series of didactic lectures focused on regenerative medicine principles, daily briefings on clinical trials to understand regenerative approaches within the clinic, laboratory experiences in stem cell culturing and 3D bioprinting, cadaver demonstrations of surgical procedures, and a regenerative medicine career panel [ 7 ].…”
Section: Resultsmentioning
confidence: 99%
“…Studies reported that while there has been funding and efforts in the biomedical science to demonstrate the safety and clinical outcomes of cell-based therapies, there appears to be lag in the translation of these technologies into clinical care [ 2 , 6 , 8 ]. This inability to translate basic science discoveries into clinical application is in part, attributed to the lack of health professionals with the knowledge and clinical skills proficiencies to provide safe and effective care [ 8 , 11 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…From the negative effects’ perspective, higher education can lead to several problems of science popularization. Specialists in the higher education system are able to suggest or guide which content or information of science popularization should be provided, and they may deceive the public intentionally or unintentionally by providing biased or even wrong information so that the understanding of the public may be misled and the outcomes of science popularization may be unwelcomed [ 12 , 23 ]. In addition, local higher education system occupies a certain proportion of the limited local resources such as labor resources, financial resources, land resources, etc., which squeezes the resources of science popularization and hinders the growth of science popularization [ 24 ].…”
Section: Literature Reviewmentioning
confidence: 99%